2015
DOI: 10.1016/j.polymdegradstab.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple extrusions and influence of PP contamination on the thermal characteristics of bottle grade recycled PET

Abstract: a b s t r a c tThe thermal characteristics of bottle grade recycled PET pellets contaminated with 5% PP prepared by multiple extrusions were studied by differential scanning calorimetry (DSC) at constant heating rate of 10 C/min for various extrusion cycles. The peak temperature of crystallization T c , the enthalpy of crystallization DH c and the degree of crystallinity X c were found to be dependent on the number of extrusion cycles. From the dependence on extrusion cycles, the analysis of the crystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
1
18
0
2
Order By: Relevance
“…Simulation of mechanical recycling by multiple processing and service life by accelerated thermal ageing to assess the effects of thermal and thermo-mechanical degradation has been previously performed for commodities [31], [34], [41], [52]- [57] such as polyethylene PE [53], polypropylene PP [53], polystyrene PS [54], [55], poly (vinyl chloride) (PVC) [57] or poly(ethylene terephthalate) PET [29], [34], [41], [56], [58], [59], among others. Mechanical recycling of biopolymers has been mainly reported for poly(hydroxybutirate) [60], poly(caprolactone) [61] and polylactide.…”
Section: Impact Of Mechanical Recycling On Pla Performancementioning
confidence: 99%
“…Simulation of mechanical recycling by multiple processing and service life by accelerated thermal ageing to assess the effects of thermal and thermo-mechanical degradation has been previously performed for commodities [31], [34], [41], [52]- [57] such as polyethylene PE [53], polypropylene PP [53], polystyrene PS [54], [55], poly (vinyl chloride) (PVC) [57] or poly(ethylene terephthalate) PET [29], [34], [41], [56], [58], [59], among others. Mechanical recycling of biopolymers has been mainly reported for poly(hydroxybutirate) [60], poly(caprolactone) [61] and polylactide.…”
Section: Impact Of Mechanical Recycling On Pla Performancementioning
confidence: 99%
“…However, the T cc of PP decreased significantly with the addition of 1% EAG. This difference in outcome can also be attributed to EAG being more compatible with PP than with PET; thus, EAG permeates into PP and hinders crystal formation [4,20]. Table 1 shows the DMA results for the PET/PP blends with the various EAG contents.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…These plastics may be sensitive to thermal and hydrolytic degradation but the knowledge of how such contamination affects thermal and mechanical properties is hard to predict and this is not well studied. It has been shown that PET is sensitive to contamination and that small amounts of contaminants may lead to cloudiness [3]. Furthermore, while plastics such as HDPE and polypropylene (PP) are not dried before processing, many biopolymers are hygroscopic and need to be carefully dried before melt processing.…”
Section: Introductionmentioning
confidence: 99%